Instruments to assess knowledge about the prevention of pressure ulcers in intensive care units: A scoping review protocol - Ana Jorge Marques; José Alves; Catarina Marinheiro; Patrícia Coelho; Paulo Alves (RevSALUS)
Introduction: Pressure ulcers represent a significant healthcare challenge, impacting quality of life and increasing costs associated with care. Understanding the factors that influence prevention strategies is crucial for improving outcomes. However, gaps in healthcare professionals' knowledge remain a major barrier, underscoring the need for a reliable tool to assess their understanding of pressure ulcer prevention. Objective: To map the existing scientific evidence on instruments designed to evaluate healthcare professionals' knowledge of pressure ulcer prevention in intensive care units. Material and Methods: The methodology outlined by the Joanna Briggs Institute for scoping reviews will be followed. This review will adhere to the PCC (Population, Concept, Context) structure: health care professionals as the population, knowledge assessment instruments for pressure ulcer prevention as the concept, and intensive care units as the context. A comprehensive search will be conducted in electronic databases (CINAHL Complete, MedicLatina, MEDLINE Complete; PubMed, Web of Science Core Collection, SciElo, and SCOPUS) and grey literature sources. Titles and abstracts will be independently screened by two reviewers, with any disagreements resolved through discussion or the involvement of a third reviewer. Finally, relevant articles will be analyzed, data will be extracted, and findings will be presented in a narrative format, either as a table or text, according to what best suits the review's objectives.